Teaching Reading by Using TPRC Strategy in Understanding Recount Text - Mirla Sarah Muthmainnah (Research in English and Education Journal, 2018)
This study is aimed at examining whether or not the use of TPRC strategy can improve students’ reading skill in understanding reading text. The researcher focuses on the application of TPRC strategy in teaching reading. The type of text that is taught was recount text in the form of multiple choice. The study was conducted at SMPN 1 Kuta Baro Aceh Besar. Quantitative approach with pre-experimental type of one group pre-test post-test design was used. The data were obtained from the pre-test, treatment and post-test. From the result of the study, it revealed that the average score of the students on the pretest is 49.29, while on the posttest is 80.24. Moreover, the researcher found that the t-score in this research is higher than the score of t-table (ts = 4   tt = 2.086). It shows that there is a significant improvement on students’ reading skill after the implementation of TPRC strategy. It means that TPRC strategy can be one of the alternative strategies used by the teacher in teaching reading skill. It is recommended to the English teachers to use TPRC strategy in teaching reading because this strategy is one of an appropriate strategies to improve students’ reading skill.